Hubungan Minat dan Tingkat Perhatian Orang Tua dengan Hasil Belajar IPS Peserta Didik di SMP Negeri 6 Palangka Raya - Suyati, Endang Sri (Anterior Jurnal, 2013)
This study aims to determine the relationship of interest and level of parents with social studies learning outcomes of students in Palangka Raya 6 Public Middle School. The research method used in this study is a correlational method. In this study the population of class VIII students was 252 people. So the researchers took a sample of 152 students. MANY in this study are called sample research. The variables in this study there are 3 (three) variables, namely the interest-free variables and the level of parents, while the variables are the results of social studies learning. Data writing techniques use questionnaire and test techniques, and analysis techniques are used multiple. From the data analysis, the results of the study were obtained. (1) There was a positive relationship between interest in learning and the results of social studies learning of students, with an explicit coefficient of rX1Y = 0.521. This correlation is significant in the population. (2) There is a positive relationship between parents with social studies learning outcomes of students, with a secret coefficient of rX2Y = 0.496. This correlation is significant in the population. (3) There is a positive relationship between interest and parents with social studies learning outcomes of students, with an explicit coefficient of R = 0.52 Fhit (27.04)> Ftab (3.07). This correlation is significant in the population.